ANALISIS LOYALITAS MEREK PADA PRODUK SEPEDA MOTOR MENGGUNAKAN MARKOV CHAINS - Rosyidi, Cucuk Nur; Aisyati, Azizah; Ramadhani, Fitria (Industrial and Systems Engineering Assessment Journal (INASEA), 2012)
The aim of this research is to analyze the probability of customer to switch from one brand of motorcycle to another. In this research, Markov Chains is used to analyze the switching probability. This research begins with identification of the initial marketing variables. In order to analyze brand loyalty with Markov Chains, three types of motorcycle from economic under-bone class (110-115cc) have been selected namely Absolute Revo, Vega ZR, Smash Titan and other types outside the class are used as comparison. Mann Whitney U Test is used to examine whether there are differences on marketing variables between men and women when selecting their motorcycle. The result of this research shows that the most loyal customer is in the type of motorcycle outside the economic underbone class. The most affecting variables that determine the existing motorcycle preferences is the availability of spareparts and the number of authorized service center for Absolute Revo, comfortable while driving for Vega ZR, and reliability motorcycle engine for Smash Titan and other types. The most variables that determine switching to another type of motorcycle is the product innovation. The results of Mann Whitney U test show that there are significant differences in marketing variables between male and female in existing motorcycle preferences which are motorcycle design and engine specifications.